TNF-α-induced oxidative stress and endothelial dysfunction in EA.hy926 cells is prevented by mate and green coffee extracts, 5-caffeoylquinic acid and its microbial metabolite, dihydrocaffeic acid. (3rd April 2019) - Wang, Shenli; Sarriá, Beatriz; Mateos, Raquel; Goya, Luis; Bravo-Clemente, Laura
Abstract: The main phenol in mate and coffee, 5-caffeoylquinic-acid (5-CQA), and its relevant microbial metabolites, dihydrocaffeic (DHCA) and dihydroferulic (DHFA) acids, have shown oxidative-stress protective effects in HepG2 cells. To evaluate possible endothelial-protective effects of the extracts and compounds, endothelial EA.hy926 cells were pre-treated with yerba mate (YME) and green coffee bean (GCBE) phenolic extracts, 5-CQA, DHCA and DHFA and afterwards stressed with tumour-necrosis-factor-alpha (TNF-α). Then oxidative-stress markers and endothelial-nitric-oxide-synthase levels were studied. TNF-α (10 ng/mL, 24 h) depleted reduced glutathione (GSH) and eNOS levels, increased reactive oxygen species (ROS) production, glutathione peroxidase (GP x ) and reductase (GR) activities, and protein oxidation (carbonyl groups, CG) in EA.hy926 cells. Pre-treatment with YME, GCBE, 5-CQA, DHCA at certain physiological concentrations, lowered ROS production, recovered depleted GSH, reduced GR and GP x activities, and CG levels, and enhanced eNOS concentration.. YME, GCBE and 5-CQA show antioxidant effects in endothelial cells playing DHCA an important role in such protection; moreover, the extracts, 5-CQA, DHCA and DHFA increased eNOS levels.